Computational Pharmacokinetics and Docking Insights into Conjugated Schiff Base Scaffold for Acetylcholinesterase Inhibition - Jacob, Blessy; Karole, Sarita (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: To evaluate the pharmacokinetic profiles and docking interactions of Schiff base scaffolds as potential Acetylcholinesterase (AChE) inhibitors using computational models. Background: Schiff bases exhibit diverse biological activities, including AChE inhibition relevant for neurodegenerative disorders. Computational evaluation of their pharmacokinetics and drug-likeness aids in prioritising ligands for further experimental validation. Objectives: To assess pharmacokinetics, drug-likeness, and molecular docking interactions of Schiff base ligands in comparison with Donepezil, an established AChE inhibitor. Materials and Methods: A series of Schiff ligands (L1-L11) was analysed for physicochemical properties, using SwissADME. Docking of the molecule and their studies were carried out with AutoDock Vina to investigate the binding interactions of the compounds with acetylcholinesterase (AChE), using its crystal structure (PDB ID: 1EVE) as the target. Medicinal chemistry filters were applied to assess synthetic feasibility and potential assay interference. Results: The Schiff base ligands (L1-L11) showed drug-like properties, good solubility, high GI absorption, and predicted BBB penetration in select cases. All passed drug-likeness rules with a bioavailability score of 0.55 and low medicinal chemistry alerts. Docking revealed stable AChE binding, supporting their potential as effective AChE inhibitors. Conclusion: Schiff base scaffolds demonstrate favourable pharmacokinetic properties, drug-likeness, and stable docking interactions with AChE.
Keywords: Schiff Base; Acetylcholinesterase Inhibition; in silico Pharmacokinetics; Molecular; Docking; Drug-likeness; ADME Profiling